The first time I thought I was dying - Walker, Sarah 1991- (University of Queensland Press, 2021)
A dazzling collection of essays that unpacks our unruly bodies and minds and questions why we are taught to fear and punish them, from an exciting and award-winning new author. We live in a world that expects us to be constantly in control of ourselves. Our bodies and minds, though, have other ideas. In this striking debut, artist and writer Sarah Walker wrestles with the awkward spaces where anatomy meets society- body image and Photoshop, phobias and religion, sex scenes and onstage violence, death and grief. Her luminous writing is at once specific and universal as she mines the limits of anxiety, intimacy and control. Sharp-witted and poignant, this collection of essays explores our unruly bodies and asks how we might learn to embrace our own chaos
Keywords: Körper; Leib-Seele-Problem; Körperbild; Walker, Sarah / 1991-; Australian essays / 21st century; Essays; Australian essays; 2000-2099; Aufsatzsammlung